Chapter 2 The Saturation of Racial Inequities in the United States - Gooden, Susan T. (Taylor & Francis, 2014)
In this compelling book the author contends that social equity--specifically racial equity--is a nervous area of government. Over the course of history, this nervousness has stifled many individuals and organizations, thus leading to an inability to seriously advance the reduction of racial inequities in government. The author asserts that until this nervousness is effectively managed, public administration social equity efforts designed to reduce racial inequities cannot realize their full potential.